Effect of functional classification on the swimming race segments during the 2012 London Paralympic Games - Pérez-Tejero, J.; Veiga, S.; Almena, A.; Navandar, A.; Navarro, E. (International Journal of Performance Analysis in Sport, 2017)
The aims of the present research were (1) to characterise the individualised race segments configuration (start, turn and free swimming) of Paralympic swimmers and (2) to examine the influence of the swimmers` functional classification on their race segments configuration. Finalists (248 men and 264 women) in the 100 m swimming events of the 2012 London Paralympic Games were distributed in five different subgroups based on their functional class designation and race performances were video-analysed with 2D-DLT algorithms. The start and turn distances of Paralympic swimmers in the 100 m events did not coincide with the traditional 10-15 m segments and they depended on the swimmer`s functional group (?2 = 0.48), as longer start and turn distances were observed according to the lower degree of impairment of swimmers. However, no differences were observed in the start and turn distances of the least physically impaired, the visually and the intellectually impaired swimmers (S8-S14), regardless of the stroke and gender. These results indicate that, in terms of the race segments configuration, there is no evidence to support the classification of S8-S14 swimmers in different functional classes.